Continuous microfluidic assembly of biodegradable poly(beta‐amino ester)/DNA nanoparticles for enhanced gene delivery. Issue 6 (12th April 2017) - Wilson, David R.; Mosenia, Arman; Suprenant, Mark P.; Upadhya, Rahul; Routkevitch, Denis; Meyer, Randall A.; Quinones‐Hinojosa, Alfredo; Green, Jordan J.
Abstract: Translation of biomaterial‐based nanoparticle formulations to the clinic faces significant challenges including efficacy, safety, consistency and scale‐up of manufacturing, and stability during long‐term storage. Continuous microfluidic fabrication of polymeric nanoparticles has the potential to alleviate the challenges associated with manufacture, while offering a scalable solution for clinical level production. Poly(beta‐amino esters) (PBAE)s are a class of biodegradable cationic polymers that self‐assemble with anionic plasmid DNA to form polyplex nanoparticles that have been shown to be effective for transfecting cancer cells specifically in vitro and in vivo . Here, we demonstrate the use of a microfluidic device for the continuous and scalable production of PBAE/DNA nanoparticles followed by lyophilization and long term storage that results in improved in vitro efficacy in multiple cancer cell lines compared to nanoparticles produced by bulk mixing as well as in comparison to widely used commercially available transfection reagents polyethylenimine and Lipofectamine® 2000. We further characterized the nanoparticles using nanoparticle tracking analysis (NTA) to show that microfluidic mixing resulted in fewer DNA‐free polymeric nanoparticles compared to those produced by bulk mixing. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1813–1825, 2017.